Microglia-Dependent and Independent Brain Cytoprotective Effects of Mycophenolate Mofetil During Neuronal Damage - Kleine, Joshua; Hohmann, Urszula; Hohmann, Tim; Ghadban, Chalid; Schmidt, Miriam; Laabs, Sebastian; Alessandri, Beat; Dehghani, Faramarz (Frontiers in Aging Neuroscience, 2022)
Acute lesions of the central nervous system often lead to permanent limiting deficits. In addition to the initial primary damage, accompanying neuroinflammation is responsible for progression of the damage. Mycophenolate mofetil (MMF) as a selective inhibitor of inosine 5-monophosphate dehydrogenase (IMPDH) was shown to modulate the inflammatory response and promote neuronal survival. The application of neuroprotective therapeutics early after neuronal damage to curb the spread and for a short period of time is a fundamental requirement for a successful immunomodulation approach. This study was designed to evaluate whether MMF can still mediate neuroprotection when applied in definite short periods. Furthermore, the role of microglia were assessed. Also temporal changes in IMPDH2 protein expression were examined. Organotypic hippocampal slice cultures (OHSC) were used as an in vitro model and excitotoxically lesioned by treatment with N-methyl-aspartate (NMDA). Clodronate (Clo) was used to deplete microglia and to analyze MMF mediated microglia independent effects. In primary glial cell cultures treated with lipopolysaccharide, the temporal expression of IMPDH2 was studied. In excitotoxically lesioned OHSC a significant neuroprotective effect was observed within a time window between 8 h-36 h but not within 8 h-24 h after NMDA damage. MMF mediated effects were mainly observed for microglia at 24 h, 36 h, 48h after injury and further targets like astrocytes seem to be involved in protective effects after 72 h post injury. IMPDH2 expression was detected in primary microglia and astrocyte cell cultures. Our data indicate that MMF treatment in OHSC can still be started 8 h -12 h after injury and should continue until 36 h post injury. Microglia seem to be an essential mediator of the observed neuroprotective effects. A microglia-independent effect was demonstrated indicating participation of astrocytes.